
Grammar and speechIt can sometimes be difficult to discern the differences between informal and formal language, which so often comes down to a single case of word choice or order, small syntactical adjustments,...

Law and PoliticsThomas Jefferson wrote the Declaration of Independence. In the Declaration of Independence, there are many ideas about the role of government and about the rights the people should have. A big part...

Death, be not proud"Death, be not proud" is a sonnet by the iconic English metaphysical poet John Donne. The fourteenline poem, which is also referred to as "Holy Sonnet X,"deals with the fear of death, overcoming...

GrammarThe primary reason this sentence is ambiguous is because of the unclear placement and use of the word "right." In the English language, the word "right" can mean two very different things. The...

Reference'Ambiguity' means a lack of clarity or concrete detail, which can make it difficult to discern meaning. In the case of these two sentences, the lack of context and detail make it possible to...

MathGiven `\frac{dy}{dx}=\frac{1}{\sqrt{4x^2}}, y(0)=\pi` , we have to find y. So we can write, `dy=\frac{dx}{\sqrt{4x^2}}` Integrating both sides we have, `y=\int \frac{dx}{\sqrt{4x^2}}+C` Now...

MathComplete the square at the denominator: `x^4 + 2x^2 + 2 = (x^2)^2 + 2x^2 + 1 + 1 = (x^2 + 1)^2 + 1.` Now we see the substitution `y = x^2 + 1,` then `dy = 2x dx,` and the integral becomes `int...

MathBy completing the square and making simple substitution, we will reduce this integral to a table one. `x^24x = (x^2 + 4x + 4) + 4 = (x+2)^2 + 4 = 4  (x+2)^2.` Now make a substitution `y =...

MathRecall that `(arccos(x))' = 1/sqrt(1x^2)` and make the substitution `y = arccos(x),` then `dy = 1/sqrt(1x^2).` The limits of integration are from `arccos(0) = pi/2` to `arccos(1/sqrt(2)) =...

MathWe have to evaluate the definite integral: `\int_{0}^{1/\sqrt{2}}\frac{arc sinx}{\sqrt{1x^2}}dx` Let arc sinx=t Differentiating both sides we get, `\frac{1}{\sqrt{1x^2}}dx=dt`...

MathMake the substitution `u = sin(x),` then `du = cos(x) dx.` The integration limits for `u` are from `sin(0) = 0` to `sin(pi/2) = 1,` and the integral becomes `int_0^1 (du)/(1 + u^2) = arctan(1) ...

MathMake a substitution `y = 2x,` then `dy = 2 dx` and the limits of integration for `y` are from `0` to `3.` The integral becomes the table one: `int_0^3 1/(1+y^2) (dy)/2 = 1/2 (tan)^(1)(y) _(y=0)^3...

MathWe have to evaluate the integral : `\int_{0}^{\sqrt{2}}\frac{dx}{\sqrt{4x^2}}` let `x=2sin t` So, `dx=2cos t dt` When x=0, t=0 `x=\sqrt{2}, t=\pi/4` So we have,...

MathMake a substitution `x = 3y,` then `dx = 3 dy` and the limits of integration for y are from 0 to 1/18. The integral becomes a table one: `int_0^(1/18) (9 dy)/(sqrt(99y^2)) = int_0^(1/18) (3...

MathRecall that the indefinite integral is denoted as: `int f(x) dx =F(x)+C` There properties and basic formulas of integration we can apply to simply certain function. For the problem `int...

MathWe have to evaluate `\int \frac{dx}{\sqrt{14x^2}}` Let `x=\frac{1}{2} sint ` So, `dx= \frac{1}{2}cost dt` Hence we have, `\int \frac{dx}{\sqrt{14x^2}}=\int \frac{\frac{1}{2}cost...

MathWe have to evaluate the integral: `\int \frac{dx}{\sqrt{9x^2}}` let `x=3sint` So, `dx=3cost dt` Hence we have, `\int \frac{dx}{\sqrt{9x^2}}=\int \frac{3cost}{\sqrt{99sin^2t}}dt`...

MathFirst, check that the given point satisfies the equation: `arctan(1 + 0) = 0 + pi/4` is true. The slope of the tangent line is `y'(x)` at the given point. Differentiate the equation with respect to...

MathRecall that the derivative of a function f at a point x is denoted as f'(x). The given function: `f(x)= arcsin(x)+arccos(x)` has inverse trigonometric terms. We can solve for the derivative of...

MathWe use the product rule, `(uv)' = u'v + uv',` for `u = x^2` and `v = arctan(5x),` and then the chain rule: `h'(x) = 2x*arctan(5x) + x^2 (arctan(5x))' =` `= 2x*arctan(5x) + (5 x^2)/(1 + 25x^2).`

MathThe given function `f(x) = arctan(sqrt(x))` is in a inverse trigonometric form. The basic derivative formula for inverse tangent is: `d/(dx) arctan(u) = ((du)/(dx))/sqrt(1u^2)` . Using...

MathThe derivative of a function with respect to t is denoted as f'(t). The given function:` f(x) = arcsin(t^2) ` is in a form of a inverse trigonometric function. Using table of derivatives, we have...

Math`arccos(1)` Let this expression be equal to y. `y = arccos(1)` Rewriting it in terms of cosine function, the equation becomes: `cos(y) = 1` Base on the Unit Circle Chart, cosine is 1 at angles 0...

Math`arccos(1/2)` Let this expression be equal to y. `y = arccos(1/2)` Rewriting this in terms of cosine function the equation becomes: `cos(y) =1/2` Base on the Unit Circle Chart, cosine is 1/2 at...

Math`arcsin(0)` Let this expression be equal to y. `y =arcsin(0)` Rewriting this equation in terms of sine function, it becomes: `sin (y) = 0` Base on the Unit Circle Chart (see attached figure), sine...

Math`arcsin(1/2)` Let this expression be equal to y. `y =arcsin(1/2)` Rewriting it in terms of sine function, the equation becomes: `sin(y) = 1/2` Base on the Unit Circle Chart (see attached figure),...

MathTo evaluate the integral: `int_(4)^(4) 3^(x/4) dx` , we follow the formula based from the First Fundamental Theorem of Calculus: `int_a^bf(x)dx=F(b) F(a)` wherein f is a continuous and F is...

MathRecall the First Fundamental Theorem of Calculus: If f is continuous on closed interval [a,b], we follow: `int_a^bf(x)dx` = F(b)  F(a) where F is the antiderivative of f on [a,b]. This...

MathBy definition, if the function F(x) is the antiderivative of f(x) then we follow the indefinite integral as `int f(x) dx = F(x)+C` where: f(x) as the integrand F(x) as the...

MathIndefinite integral are written in the form of` int f(x) dx = F(x) +C` where: f(x) as the integrand F(x) as the antiderivative function C as the arbitrary constant known...

MathDerivative of a function h with respect to t is denoted as h'(t). The given function: `h(t) = log_5(4t)^2` is in a form of a logarithmic function. From the derivative for logarithmic functions,...

Math`y= log_3(x^23x)` The derivative formula of a logarithm is: `d/(dx) [log_a (u)] = 1/(ln(a) * u) * (du)/(dx)` Applying this formula, the derivative of the function will be: `(dy)/(dx) = d/(dx)...

Math`y=log_4(5x + 1)` The derivative formula of a logarithm is: `d/(dx) [log_a (u)] = 1/(ln(a) * u) * (du)/(dx)` Applying that formula, the derivative of the function will be: `(dy)/(dx) = d/(dx)[...

Math`f(t) = 3^(2t)/t` To take the derivative of this function, use the quotient rule `(u/v)'= (v*u'  u*v')/v^2`. Applying that, f'(t) will be: `f'(t) = (t * (3^(2t))'  3^(2t)*(t)')/t^2` `f'(t) =...

MathThe derivative of a function f at a point x is denoted as y' = f'(x). There are basic properties and formula we can apply to simplify a function such as the Product Rule provides the formula:...

MathRecall that the derivative of a function f at a point x is denoted as `y' = f'(x)` . There basic properties and formula we can apply to simplify a function. For the problem `y = x(6^(2x)),` we...

MathThe given function: `f(x)=x9^x ` has two factors since that is the same as `f(x) =x* 9^x` . In this form, we can apply the Product Rule for derivative. Product Rule provides the formula: `f(x) =...

Math`y=6^(3x4)` The derivative formula of an exponential function is: `d/(dx) (a^u) = ln(a) * a^u * (du)/dx` Applying this formula, the derivative of a function will be: `(dy)/(dx) = d/(dx)...

Math`y=5^(4x)` The derivative formula of an exponential function is: `d/(dx) (a^u) = ln(a) * a^u * (du)/(dx)` Applying this formula, the derivative of the function is: `(dy)/(dx) = d/(dx)(5^(4x))`...

MathThe derivative of f(x) with respect to x is denoted a f'(x). The given function f(x) = 3^(4x) is in exponential form which means we can apply the basic integration formula: `d/(dx)(a^u) =...

MathBy definition, the derivative of f(x) with respect to x is denoted a f'(x) where `f'(x) = lim (f(x+h) f(x))/h ` as` h>0` . Instead of using the limit of difference quotient, we may apply the...

MathTo simplify the logarithmic equation: `log_5(sqrt(x4))=3.2` , recall the logarithm property: `a^((log_(a)(x))) = x` . When a logarithm function is raised by the same base, the log cancels out...

MathTo solve a logarithmic equation, we may simplify or rewrite it using the properties of logarithm. For the given problem `log_(3)(x^2)=4.5` , we may apply the property: `a^((log_(a)(x))) = x` The...

MathIn solving a logarithmic equation, we may simplify using logarithm properties. Recall the logarithm property: `a^((log_(a)(x))) = x` . When we raise the log with the same base, the "log" will...

Math`log_2 (x1) =5` To solve, convert the equation to exponential form. Take note that if a logarithmic equation is in the form `y = log_b (x)` its equivalent exponential equation is `x= b^y` So...

MathProblem:`3(5^(x1))=86` ` ` To simplify, we divide both sides by 3: `(3(5^(x1)))/3=(86)/3` `5^(x1)=(86)/3` ` ` ` ` Take the "log" on both sides to apply the logarithm property:...

MathFor exponential equation:`2^(3z)=625` , we may apply the logarithm property: `log(x^y) = y * log (x)` . This helps to bring down the exponent value. Taking "log" on both sides:...

MathFor exponential equation: `5^(6x)= 8320` , we may apply the logarithm property: `log(x^y) = y * log (x).` This helps to bring down the exponent value. Taking "log" on both sides:...

MathProblem:` 3^(2x)=75` is an exponential equation. To simplify, we need to apply logarithm property: `log(x^y) = y*log(x)` to bring down the exponent that is in terms of x. Taking "log" on both...

Math`log_3(x) + log_3(x  2) = 1` The logarithms at the left side have the same base. So express the left side with one logarithm only using the rule `log_b (M) + log_b (N) = log_b(M*N` ). `log_3(x *...
rows
eNotes
search